EXPLORATORY FACTOR ANALYSIS AND RELIABILITY OF ‘STUDENT OUTCOME’ INSTRUMENT USING IBNU MASKAWAIH’S THEORY - Othman, Mohamad Khairi Haji; Yaakob, Mohd Faiz Mohd; Haron, Mohd. Zulhilmi; Abdullah, Shuhairimi; Zakaria, Normah; Mahzan, Saifolrudin Khalid (CENTRAL ASIA AND THE CAUCASUS, 2021)
The success of a school depends on student outcome which can be measured based on three main aspects, namely academic, co-curriculum and personality. The ineffectiveness of programs organized by schools to cultivate good values among students has led to the need for certain efficient and systematic mechanisms to be established to assess the current level of student outcome. Therefore, this study proposed the development and validation of holistic student outcome instrument based on Ibn Maskawaih's theory in the mission of shaping students according to the true Islamic mold. Quantitative method with descriptive survey study design through the distribution of questionnaires to respondents was used. A total of 209 Form 4 students were selected from 7 schools in the state of Perlis. Findings from Exploratory Factor Analysis showed that the factors of al-hikmah, as-syaja'ah and al-‘Iffah are very suitable to be used to measure the level of student outcome. Based on the al-hikmah actor, the four factors that are suitable for use are intelligence, memory, rationality and smart. Meanwhile the three factors that are suitable to be used for the al-iffah factor are politeness, generosity and harmony. Finally, there are seven factors that are suitable to be used for the as-syajaah factor, namely high minded, perseverance, mental endurance, high ideal, patience, physical endurance and courage. As a result of exploratory factor analysis (EFA), it was found that al-hikmah, al-Iffah and as- syajaah factors have been successfully discovered and are suitable for use.